Utilization of Biochar and Liquid Smoke to Increase Livestock Performance - Novia Qomariyah; Y Retnani; A Jayanegara; E Wina; I G Permana (Indonesian Center for Animal Research and Development, 2019)
Biochar and liquid smoke may be utilized as feed additives that potentially used as substitutes for antibiotics. These products are derived from the pyrolysis process that utilizes agricultural, plantation and wood residues. This paper aims to review research results regarding the use of biochar and liquid smoke as feed additives in both non-ruminants and ruminants. Information on the use of of biochar and liquid smoke in livestock are available such as the use of 0.5-1 g bamboo charcoal/ kg goat feed increased growth; addition of 0.2-0.6% corn cobs char to chicken feed showed significant increase in body weight; the addition of 0.6% biochar/ kg feed to local cattle feed increased body weight; the use of activated charcoal containing wood vinegar liquid can reduce cryptosporidiosis in goats and cattle. The opportunity to use agricultural and plantation residues as raw materials for generating biochar and liquid smoke is one of the breakthroughs in realizing the concept of sustainable and environmentally friendly of bioindustrial agriculture. The use of biochar and liquid smoke from agricultural and plantation residues is expected to increase livestock productivity.